Details of the Latina Nagara Shikhara of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here are the details of the Latina nagara (mono-spired) shikhara (superstructure) of the central shrine in the Neelkanth Mahadev Temple. It is made up of five vertical projections. The central band or the madhyalata is flanked by pratilatas. These three bands are made up of a mesh of gavaksha (dormer window) motifs. The corner bands of the shikhara have aedicules which are known as bhumikhandas, again having gavaksha designs on their surfaces. These aedicules diminish in size and are separated by flat ribbed discs. Based on this shikhara, it can be speculated that the other two shrines of the temple must have had similar Latina nagara shikharas.